Effects of employee training on job satisfaction outcomes among sport ticket sellers. (16th May 2019) - Popp, Nels; Simmons, Jason; McEvoy, Chad
As the primary revenue generators for sports organisations, salespeople play a critical role in the sport industry. Research regarding salesperson effectiveness and well-being, however, is scant within the sport management literature, and little has been empirically investigated related to the salesperson's role in sport organisations. The purpose of this study is to examine the relationship between sales training on both job satisfaction and turnover intent measures among professional sellers within sport organisations. No significant differences were found between the amount of initial sales training received and measures of job satisfaction and intent to leave the organisation. Significant differences were found, however, on two measures of on-going sales training (amount and quality) with both job satisfaction and turnover intent. The findings suggest a relationship between training and occupational satisfaction, which has important managerial implications as sport sales positions traditionally have a high rate of job turnover.